2016
DOI: 10.1016/j.ultsonch.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonically enhanced extraction of luteolin and apigenin from the leaves of Perilla frutescens (L.) Britt. using liquid carbon dioxide and ethanol

Abstract: The present study reports on the ultrasonic enhancement of the liquid carbon dioxide (CO2) extraction of luteolin and apigenin from the leaves of Perilla frutescens (L.) Britt., to which ethanol is added as a cosolvent. The purpose of this research is also to investigate the effects of the particle size, temperature, pressure, irradiation power, irradiation time, and ethanol content in the liquid CO2 solution on the extraction yield using single-factor experiments. We qualitatively and quantitatively analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…This increased the interaction of the solute and CO2. Therefore, the solubility of curcumin in USC-CO2 increase and this enhance the efficiency of extraction [17,18]. Similar to this study, Santos et al 2016 [15], who extracted cumbaru oil from the cumbaru almond using ultrasonic assisted SC-CO2 extraction, reported that the global yield of extraction increased with increasing pressure because increasing pressure increase the density of CO2.…”
Section: Effect Of Pressuresupporting
confidence: 78%
See 1 more Smart Citation
“…This increased the interaction of the solute and CO2. Therefore, the solubility of curcumin in USC-CO2 increase and this enhance the efficiency of extraction [17,18]. Similar to this study, Santos et al 2016 [15], who extracted cumbaru oil from the cumbaru almond using ultrasonic assisted SC-CO2 extraction, reported that the global yield of extraction increased with increasing pressure because increasing pressure increase the density of CO2.…”
Section: Effect Of Pressuresupporting
confidence: 78%
“…3 indicated that the extraction time for the high extraction yield and curcumin content obtained by USC-CO2 were 60 min and 90 min, respectively. The ultrasound can produce micro-stirring and solvent cavitation which can improve the extraction yield and curcumin content from turmeric due to the damage of cell wall of plant and an increase of mass transfer of solvent when ultrasound was applied in SC-CO2 extraction [17,18]. Kawamura et al 2016 [18] also found that the extraction yield of luteolin and apigenin from the leaves of Perilla frutescans were enhanced using ultrasound assisted SC-CO2 extraction.…”
Section: Effect Of Extraction Timementioning
confidence: 99%
“…Extensive research has been carried out to improve the SCF/SFE technique; this research ranges from kinetic modelling [ 36 ], sample preparation and pre-treatment by using pressing [ 37 ], ultra-sonication [ 38 ], microwave irradiation [ 39 ], enzyme-assistance [ 40 ] or, within the extraction vessel, ultrasonic-assistance [ 41 ], and a hydrothermal approach [ 42 ]. It should be noted that there are many review publications on the subject of this review, however, most have a large degree of overlap that describes SFE in relation to plant extracts [ 8 , 9 , 10 , 11 , 12 , 13 , 15 ] and food [ 14 , 16 ], and there is relative silence in the reviewed literature on the use of sonication in the assistance of SFE-based extractions.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction efficiency is predisposed by numerous factors such as polarity and concentration of solvent, material-solvent ratio, duration, temperature, pH, etc... Extensive research has been carried out to improve the supercritical fluid extraction (SC extraction) technique to optimize a specific target compound extraction. This research comprises kinetic modelling, 25 sample preparation and pre-treatment by using pressing, 26 ultrasonication, 27 microwave irradiation, 28 enzyme-assistance 29 or, within the extraction vessel, ultrasonic-assistance, 30 and a hydrothermal approach. 31 Despite there are many review publications on the subject of this review, however, most studies discuss the influence of a single factor has been discussed, while the relations between the factors on the extract yield and composition have not been studied comprehensively.…”
Section: Introductionmentioning
confidence: 99%